Differential killing of CD56-expressing cells by drug-conjugated human antibodies targeting membrane-distal and membrane-proximal non-overlapping epitopes. Issue 4 (18th May 2016) - Feng, Yang; Wang, Yanping; Zhu, Zhongyu; Li, Wei; Sussman, Robyn T.; Randall, Michael; Bosse, Kristopher R.; Maris, John M.; Dimitrov, Dimiter S.
ABSTRACT: CD56 (NCAM, neural cell adhesion molecule) is over-expressed in many tumor types, including neuroblastoma, multiple myeloma, small cell lung cancer, ovarian cancer, acute myeloid leukemia, NK-T lymphoma, neuroendocrine cancer and pancreatic cancer. Using phage display, we identified 2 high-affinity anti-CD56 human monoclonal antibodies (mAbs), m900 and m906, which bound to spatially separated non-overlapping epitopes with similar affinity (equilibrium dissociation constant 2.9 and 4.5 nM, respectively). m900 bound to the membrane proximal fibronectin type III-like domains, whereas m906 bound to the N-terminal IgG-like domains. m906 induced significant down-regulation of CD56 in 4 neuroblastoma cell lines tested, while m900-induced downregulation of CD56 was much lower. Antibody-drug conjugates (ADCs) made by conjugation with a highly potent pyrrolobenzodiazepine dimer (PBD) exhibited killing activity that correlated with CD56 down-regulation, and to some extent with in vivo binding ability of the antibodies. The m906PBD ADC was much more potent than m900PBD, likely due to higher CD56-mediated downregulation and stronger binding to cells. Treatment with m906PBD ADC resulted in very potent cytotoxicity (IC50: 0.05–1.7 pM). These results suggest a novel approach for targeting CD56-expressing neuroblastoma cells. Further studies in animal models and in humans are needed to find whether these antibodies and their drug conjugates are promising candidate therapeutics.